2014
DOI: 10.1089/ten.teb.2013.0543
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Tissue Engineering with Biphasic Scaffold: Current Strategies and Techniques

Abstract: The management of osteoarthritis (OA) remains challenging and controversial. Although several clinical options exist for the treatment of OA, regeneration of the damaged articular cartilage has proved difficult due to the limited healing capacity. With the advancements in tissue engineering and cell-based technologies over the past decade, new therapeutic options for patients with osteochondral lesions potentially exist. This review will focus on the feasibility of tissue-engineered biphasic scaffolds, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 113 publications
0
92
0
1
Order By: Relevance
“…Cartilage nutrition is supported by the subchondral bone plate, thus any damages such as osteochondral defects can prevent regenerating cartilage. In such cases, using a biodegradable scaffold as the subchondral bone plate can enhance the cartilage healing process [112][113][114]. Ideal scaffolds in subchondral bone plate tissue engineering should provide adequate mechanical stability, appropriate pore size, sufficient porosity, and optimized programmed degradation.…”
Section: Cartilagementioning
confidence: 99%
“…Cartilage nutrition is supported by the subchondral bone plate, thus any damages such as osteochondral defects can prevent regenerating cartilage. In such cases, using a biodegradable scaffold as the subchondral bone plate can enhance the cartilage healing process [112][113][114]. Ideal scaffolds in subchondral bone plate tissue engineering should provide adequate mechanical stability, appropriate pore size, sufficient porosity, and optimized programmed degradation.…”
Section: Cartilagementioning
confidence: 99%
“…Engineering multilayer scaffolds with controlled properties in each layer could allow the replication of the local microenvironment of the osteochondral tissue. For satisfying the biological requirements, an osteochondral implant should ideally have a rigid osseous layer (to support the overlying cartilage and integrate with the native bone) and a chondral layer (to enable the seeding and proliferation of chondrocytes or mesenchymal stem cells and subsequent deposition of cartilaginous extracellular matrix) [31]. Moreover, the integrated materials can transfer physical or chemical stimuli from the cartilage to the bone layers, because the interface tissue is exposed to shear forces over a large range of motion.…”
Section: Bone-like Scaffolds: Bioceramic and Nano-composite Monolithimentioning
confidence: 99%
“…They suggested that by designing osteochondral scaffolds with a tissue-specific architecture, it may be possible to enhance osteochondral repair within a shorter time frame. 12 Shimomura et al 13 also discussed thoroughly the use of tissue-engineered biphasic scaffolds for osteochondral repair, which can mimic the native osteochondral complex. I agree that it is important to understand the process from the bone area via the calcified zone into pure cartilaginous tissue to one day be able to restore a cartilage defect by regeneration.…”
Section: Cell-seeding Layersmentioning
confidence: 99%